Has the sea changed? qualitative on the views of fishermen in the east coast zone of peninsular - Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; D’Silva, Jeffrey Lawrence; Uli, Jegak (Science Publications, 2011)
Problem statement: Pressure from the uncontrolled human activities had caused damages to our environment. The sea, as one of the environment components has also suffered from these activities. Fishermen, whom depend on the sea for their income and sources of protein, can be one of the groups who are suffering the most. This study intends to discover the perception of this group on the current situation of the sea, their perception on the quantity and the quality of the sea fauna, their perception on the possible factors that contribute to these changes and impacts of these changes on their socio-economic activities. Approach: This was a qualitative study whereby four in-depth interviews were conducted with the fishermen of the east coast zone of Peninsular Malaysia whom their main fishing area was on South China Sea. The data then were transcribed verbatim and analyzed. Results: Data gained had proven that the fishermen agreed that the current situation on the South China Sea was not anymore similar to their early day as a fisherman. The weather nowadays was ifficult to be predicted as there are changes in the trend of sea current, waves and temperature. They also agreed that the quality and quantity of the flora and fauna in their catching areas were lesser compared to the past. There are number of possibilities that can contribute to these changes which were illegal bottom trawling, foreign fishermen intrusion, climate change and fishing pressure. All of these according to them were affecting their socio-economic activities. Conclusion/recommendation: Based on the data gained, it is recommended that more monitoring programs can be conducted to reduced illegal bottom trawling activities; Program such as Rakan Cop which is introduced by Royal Police of Malaysia can be practiced among the concern agencies and fishermen. A number of programs to increase awareness among the fishermen on the danger of illegal bottom trawling activities, threats of the climate change and the importance for them to save usage of energy (eg: Fuel) can also be conducted. Some effective actions taken by other countries to overcome their fishing pressure might also have the potential to be practiced in Malaysia.